Screening of phytochmical, antioxidant and larvicidal activities of Litsea quinqueflora - Kokkaiah Irulandi; Gandhi Theivandran; Samy Eswaran (Revista Electronica de Veterinaria, 2023)
The present study is investigate the chemical composition, antioxidant, antimicrobial and larvicidal activities of the essential oils from the leaves of Litsea quinqueflora (Dennst.) Suresh in Mehamalai Hills. The essential oils were extracted by hydrodistillation and analyzed by GC and GC-MS. Sesquiterepenes were the major class of compounds present in the L.quinquiflora leaf oil. The antimicrobial activity of essential oils was evaluated by agar well method. Essential oils exhibited remarkable inhibitory activity against all tested Gram-positive bacteria. The maximum zone of inhibition noted in methanol extract against S. hominis (13.66 mm). Furthermore, the larvicidal activity of essential oils was tested using fourth-instar larvae of C. quinquefasciatus and A. Aegyptii. At 1000 ppm concentration the methanol extract showed 61 % mortality against A. aegyptii and 76 % against C. quinquefasciatus at 24 h. Our findings demonstrate that the essential oil extracted from Litsea quinqueflora are potential sources of natural antimicrobials and can act as inexpensive mosquito larvicidal agents.